A question of choice - Goseco, Petronila S.
The findings in this study further validate some important viewpoints in current language theory and research on bilingualism. The multicultural character of Filipino is once again strongly evidenced by the data. Results from the surveys done along language use and choice still present an interesting picture of a Filipino people desiring to achieve economic growth while trying to achieve unity and independence.
Keywords: Language policy -- Philippines; Bilingualism -- Philippines